Serogroup C meningococci in Italy in the era of conjugate menC vaccination - Stefanelli, Paola (BioMed Central, 2009)
BACKGROUND: To assess changes in the pattern of Invasive Meningococcal Disease (IMD) in Italy after the introduction of conjugate menC vaccine in the National Vaccine Plan 2005–2007 and to provide information for developing timely and appropriate public health interventions, analyses of microbiological features of isolates and clinical characteristics of patients have been carried out. In Italy, the number of serogroup C meningococci fell progressively following the introduction of the MenC conjugate vaccine, recommended by the Italian Ministry of Health but implemented according to different regional strategies. METHODS: IMD cases from January 2005 through July 2008 reported to the National Meningococcal Surveillance System were considered for this study. Serogrouping and sero/subtyping were performed on 179 serogroup C strains received at the National Reference Laboratory of the Istituto Superiore di Sanità. Antibiotic susceptibility testing was possible for 157 isolates. MLST (Multilocus sequence typing), porA VRs (Variable Region) typing, PFGE (Pulsed Field Gel Electrophoresis), VNTR (Variable Number Tandem Repeats) analyses were performed on all C:2a and C:2b meningococci (n = 147), following standard procedures. RESULTS: In 2005 and 2008, IMD showed an incidence of 0.5 and 0.3 per 100,000 inhabitants, respectively. While the incidence due to serogroup B remained stable, IMD incidence due to serogroup C has decreased since 2006. In particular, the decrease was significant among infants. C:2a and C:2b were the main serotypes, all C:2a strains belonged to ST-11 clonal complex and all C:2b to ST-8/A4. Clinical manifestations and outcome of infections underlined more severe disease caused by C:2a isolates. Two clusters due to C:2a/ST-11 meningococci were reported in the North of Italy in December 2007 and July 2008, respectively, with a high rate of septicaemia and fatal outcome. CONCLUSION: Public health surveillance of serogroup C invasive meningococcal disease and microbiological/molecular characterization of the isolates requires particular attention, since the hyper-invasive ST-11 predominantly affected adolescents and young adults for whom meningococcal vaccination was not recommended in the 2005–2007 National Vaccine Plan.